Factors Affecting the Revenue of MTE Mechanical Private Limited Company - Kok Ban Teoh; Miguel Cordova; Tin Phang Ooi; Maryam Tayyiba; Uma Warrier; Siti Fatini Binti Azahar; Pei Fen Khow; Ming Hao Loo; Daisy Mui Hung Kee; Chee Woh Liew; Chuan Heng Low; Wei Xuan Chin (Journal of the Community Development in Asia (JCDA), 2021)
MTE Mechanical Private Limited Company is a manufacturing company located at Batu Maung, Malaysia producing fabricated metal products. During 2020, the company’s revenue has significantly decreased compared to the previous year. Therefore, the purpose of this research is to identify the factors which affect the revenue of the company. Online interviews were used to collect information from the company’s owner and three of their customers. The present study found that the delivery service and product’s quality of the company are the major issues having effects upon the company’s revenue. Moreover, the findings of the present study would benefit the company.